Georeferencing of the seismological and accelerographic stations of the seismo-logical observatory of the University of Quindio implementing the system of positioning GNSS (Revista de Investigaciones Universidad del Quindío, 2018)
The Seismological Observatory of the Universidad del Quindio (OSQ) has 6 seismological stations (Bolivar, Penas Blancas broadband, Caicedonia, Modin, Rivera and Penas Blancas analogous) and 3 accelerographic stations (Uniquindio, Calarca and Genova), strategically distributed in the department of Quindio and Valle del Cauca, which carry out the monitoring of seismic activity in the area. These stations are not georeferenced, for this reason, the Positioning System (GNSS) is implemented using high-precision instruments with the help of specialized software to achieve greater accuracy in the compilation of data and therefore improve the location of seismic events recorded in the (OSQ). In order to collect the information, it was necessary to carry out measurement campaigns through the GNSS Planning Online Software, which indicates the days when satellites are most available to obtain greater precision. For the data processing, the post-processing method was used to correct the systematic errors that occur during the capture of information in the field and later an adjustment was made with the TopCon Tools software to deliver results with the least possible error. As a final product of the investigation, a catalogue with the geographic coordinates of the stations duly georeferenced and located in a map of the region is delivered to (OSQ), leaving an input that favors the activities carried out by this agency.
Keywords: Georeferencing; GNSS positioning system; post-processing; differential or relative positioning